2018
DOI: 10.1016/j.nicl.2018.02.033
|View full text |Cite
|
Sign up to set email alerts
|

DEWS (DEep White matter hyperintensity Segmentation framework): A fully automated pipeline for detecting small deep white matter hyperintensities in migraineurs

Abstract: Migraineurs show an increased load of white matter hyperintensities (WMHs) and more rapid deep WMH progression. Previous methods for WMH segmentation have limited efficacy to detect small deep WMHs. We developed a new fully automated detection pipeline, DEWS (DEep White matter hyperintensity Segmentation framework), for small and superficially-located deep WMHs. A total of 148 non-elderly subjects with migraine were included in this study. The pipeline consists of three components: 1) white matter (WM) extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Thus, we have developed a fully automated, machine learning-based, segmentation method for detecting small deep WMH in migraineurs and showed its superiority compared to pre-existing segmentation tools (Fig. 1) [64]. Recently, we also developed a deep learning-based detection method for the detection of small deep WMHs in migraineurs and obtained a slightly better result [65].…”
Section: Methodological Issue: Detection Of Wmhmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, we have developed a fully automated, machine learning-based, segmentation method for detecting small deep WMH in migraineurs and showed its superiority compared to pre-existing segmentation tools (Fig. 1) [64]. Recently, we also developed a deep learning-based detection method for the detection of small deep WMHs in migraineurs and obtained a slightly better result [65].…”
Section: Methodological Issue: Detection Of Wmhmentioning
confidence: 97%
“…However, this method is less applicable for larger studies as it has an inter-rater/intra-rater reliability issue and lacks quanti- We compared several preexisting segmentation methods for detecting small deep WMHs in migraineurs aged 18 to 50 years, and their performance were poor in sensitivity and specificity [64]. Thus, we have developed a fully automated, machine learning-based, segmentation method for detecting small deep WMH in migraineurs and showed its superiority compared to pre-existing segmentation tools (Fig.…”
Section: Methodological Issue: Detection Of Wmhmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of them also used additional datasets or patient data from clinics. Out of 37, twelve studies reported using data from prospective studies or clinics (Atlason et al, 2019;Bowles et al, 2017;Guerrero et al, 2017;Hong et al, 2020;Moeskops et al, 2018;Ling et al, 2018;Park et al, 2018;Qin et al, 2018;Rincón et al, 2017;Roy et al, 2015;Sundaresan et al, 2019;Wang et al, 2015). Four studies used data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) (Sudre et al, 2017;Dadar et al, 2017a;Rachmadi et al, 2018Rachmadi et al, , 2020, of which only two declared the subset used (Rachmadi et al, 2018(Rachmadi et al, , 2020.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Applications of artificial intelligence to stroke are increasing, and include diagnosis of acute ischemic stroke [36], prediction of stroke [37], predicting outcome after endovascular therapy [38], and pervasive health monitoring using smart monitoring devices [39]. Several studies of machine learning techniques to measure the severity of subclinical white matter changes have recently been reported [40], such as automated white matter segmentation algorithms to measure the severity of white matter hyperintensities in lacunar stroke [41,42], support vector machine techniques to classify the burden of perivascular space in the basal ganglia region [43], and cortical and subcortical volumetric segmentation of diffusion tensor imaging feature vectors [44].…”
Section: Recent Advances: Machine Learning Techniquesmentioning
confidence: 99%